Tribulus Terrestris for Female Sexual Dysfunction: A Systematic Review - Ana Luiza Cabrera Martimbianco; Rafael Leite Pacheco; Fábia Lima Vilarino; Carolina de Oliveira Cruz Latorraca; Maria Regina Torloni; Rachel Riera (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2020)
Abstract Objective We performed a systematic review to assess the effectiveness and safety of Tribulus terrestris to treat female sexual dysfunction (FSD). Data sources We performed unrestricted electronic searches in the MEDLINE, CENTRAL, EMBASE, LILACS, CINAHL, PsycINFO,WHO-ICTR, Clinicaltrials.gov and OpenGrey databases. Selection of studies We included any randomized controlled trials (RCTs) that compared T. terrestris versus inactive/active interventions. After the selection process, conducted by two reviewers, 5 RCTs (n = 279 participants) were included. Data collection Data extraction was performed by two reviewers with a preestablished data collection formulary. Data synthesis Due to lack of data and clinical heterogeneity, we could not perform meta-analyses. The risk of bias was assessed by the Cochrane Risk of Bias (RoB) tool, and the certainty of evidence was assessed with Grading of Recommendations, Assessment, Development and Evaluations (GRADE). Results After 1 to 3 months of treatment, premenopausal and postmenopausal women randomized to T. terrestris had a significant increase in sexual function scores. Three months of treatment with T. terrestris showed a significant increase in the serum testosterone levels of premenopausal women. There was no report of serious adverse events, and none of the studies assessed health-related quality of life. The certainty of the evidence was very low, whichmeans that we have very little confidence in the effect estimates, and future studies are likely to change these estimates. Conclusion MoreRCTs are needed to supportor refute the use of T. terrestris. The decision to use this intervention should be shared with the patients, and the uncertainties around its effects should be discussed in the clinical decision-making process. Number of Protocol registration in PROSPERO database: CRD42019121130